The experience of waste management in the food industry of Azerbaijan - Emin Huseynov (Academics and Science Reviews Materials, 2023)
Food waste management is a pressing research area aligning with green economic principles. This article examines Azerbaijan’s approach to food waste management, focusing on statistical data and methods. Through statistical analysis, it highlights trends and challenges in the country’s food industry waste management. The article explores theoretical and practical strategies, from policy frameworks to waste reduction and sustainable disposal methods. By studying Azerbaijan’s experience, this research contributes to the global discourse on sustainable food waste management.